The Model of Information Technology Utilization in Rural Areas of Indonesia Based on 4G LTE - Thomas Budiman; Usman Gultom; Tomi Defisa (Journal of International Conference Proceedings, 2021)
4G-LTE has become game changer in the GSM era especially in a developing country which has limited connectivity to the internet world. Having this limited capability, several rural areas in Indonesia has been suffered of its internet connection need. They need to visit nearest city just to used better internet connection. Facing industry 4.0 era, it is normal to have internet connection everywhere that supports industrial activities from all levels ranging from home industry to heavy industry, to win the competitive market. The people should get sufficient internet connection to support their daily activity. Nowadays, with COVID-19 pandemic has transformed all human being to adapt this fast-growing technology, just to survive from the pandemic. What was on site activity now has become remotely conducted activity (mostly using internet connection). 4G-LTE technology that is widely available for telecommunication in Indonesia, should also adopted to support daily activity during and beyond pandemic situation. This study employs common telecommunication devices combined with networking devices targeted to achieve the same utilization of the devices when implemented in most common places like offices in major cities, that in the end brings internet connection to places where usually no internet connection or blank spots occurred in rural areas.